2018
DOI: 10.5114/aoms.2017.69383
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of DNA fragmentation factor 40, DNA fragmentation factor 45, and B-cell lymphoma 2 protein in normal human endometrium and uterine myometrium depends on menstrual cycle phase and menopausal status

Abstract: IntroductionDNA fragmentation factors 40 and 45 (DFF40 and DFF45) are final executors of apoptosis, and B-cell lymphoma 2 (Bcl-2) is a well-recognized apoptosis inhibitor. We aimed to evaluate DFF40, DFF45 and Bcl-2 immunoexpression in the normal human endometrium with respect to the glandular and stromal layer and in uterine myometrium.Material and methodsDFF40, DFF45, and Bcl-2 expression was assessed via immunohistochemistry in the endometrium and myometrium collected postmenopausally and premenopausally du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These findings strongly suggest that Bcl‐2 loss may be a marker of endometrial neoplasia, and they are compatible with scientific evidence on Bcl‐2 physiology. In fact, as Bcl‐2 under hormonal control, its expression is expected to be high in benign proliferative conditions caused by the action of estrogens such as proliferative endometrium and benign endometrial hyperplasia …”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that Bcl‐2 loss may be a marker of endometrial neoplasia, and they are compatible with scientific evidence on Bcl‐2 physiology. In fact, as Bcl‐2 under hormonal control, its expression is expected to be high in benign proliferative conditions caused by the action of estrogens such as proliferative endometrium and benign endometrial hyperplasia …”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, BCL-2 expression levels were found to increase in endometrial tissue of proliferative phase in comparison with in endometrial tissue of secretory phase and for menopausal endometrial tissue as well. However, there was no signi cant difference in terms of myometrial tissues in different hormonal status in terms of BCL-2 levels in the same study (17). It is a well-known fact that menopause has a negative effect on the uterus by mediating atrophy.…”
Section: Discussionmentioning
confidence: 57%
“…A -Creatinine, B -total urea nitrogen and C -bilirubin. There is a significant difference compared with data gathered before surgery (p < 0.05) lowing the removal of the T-tube [30]. Now the researchers and surgeons focus on the new therapy for the CBD and the choice of the researchers and surgeons is a biodegradable stent.…”
Section: Discussionmentioning
confidence: 94%